2007
DOI: 10.1002/jgm.1130
|View full text |Cite
|
Sign up to set email alerts
|

Hexamethylene bisacetamide leads to reduced helper virus‐free HSV‐1 amplicon expression titers via suppression of ICP0

Abstract: The Herpes simplex virus (HSV)-derived amplicon vector has evolved into a promising gene transfer platform for widespread DNA delivery in gene replacement strategies and vaccine development given its ease of molecular manipulation, large transgene capacity, and transduction efficiencies of numerous cell types in vivo. The recent development of helper virus-free packaging methodologies bodes well for this vector system in its eventual implementation as a clinically viable therapeutic modality. For realization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
(74 reference statements)
1
4
0
Order By: Relevance
“…Notably, ICP0 expression was downregulated by USP9X, in contrast to other USP9X-interacting proteins. Accordingly, we found that USP9X depletion increased viral replication, in agreement with a previous report [ 4 ] demonstrating that ICP0 enhances HSV-1 replication. These observations suggested that USP9X negatively regulates ICP0 expression to inhibit viral replication, although we cannot exclude the possibility that USP9X may suppress HSV-1 replication through other pathways.…”
Section: Discussionsupporting
confidence: 93%
“…Notably, ICP0 expression was downregulated by USP9X, in contrast to other USP9X-interacting proteins. Accordingly, we found that USP9X depletion increased viral replication, in agreement with a previous report [ 4 ] demonstrating that ICP0 enhances HSV-1 replication. These observations suggested that USP9X negatively regulates ICP0 expression to inhibit viral replication, although we cannot exclude the possibility that USP9X may suppress HSV-1 replication through other pathways.…”
Section: Discussionsupporting
confidence: 93%
“…4 As, as already quoted, one important role of ICP0 is to induce degradation of several ND10 constitutive proteins that are thought to contribute to silencing of gene expression, including PML and Sp100, these results lend further support to the hypothesis that an inherent antiviral mechanism is partially responsible for the silencing of ampliconmediated transgene expression in human fibroblasts. Lastly, the observation that the reduction of particleassociated ICP0 levels, that results from packaging the amplicon genome in the presence of the transcriptional regulator hexamethylene bisacetylamide, also results in reduced transgene expression, 7 provides further evidence for a role of ICP0 in suppressing silencing mechanisms that repress amplicon-mediated transgene expression.…”
Section: Herpes Simplex Virus Type 1-based Vectors Al Epsteinmentioning
confidence: 94%
“…Furthermore, siRNA downregulation of Sp100 and Daxx, two regulatory proteins that localize to PML bodies, resulted in at least 5-fold enhancement in the number of GFP-expressing normal human fibroblasts infected with standard amplicons (Tsitoura & Epstein, unpublished observations). Lastly, the observation that the reduction of particle-associated ICP0 levels, which results from packaging the amplicon genome in the presence of the transcriptional regulator hexamethylene bisacetylamide, also results in reduced transgene expression (Burris et al 2008), provides further evidence for a role of ICP0 in suppressing silencing mechanisms that repress GFP expression.…”
Section: Expression Of the Transgenic Cassettesmentioning
confidence: 99%